Chronobiological insights in plyometric jump training: optimizing sport-performance adaptations for volleyball players - Zhu, M.; Cui, Z. (International Journal of Sports Physiology and Performance, 2024)
Purpose The objective of this study was to investigate the effects of morning versus evening plyometric training (PT) on performance adaptations in male volleyball players.